2006
DOI: 10.1038/sj.onc.1209628
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin underpins CD44-promoted invasion and adhesion of breast cancer cells to bone marrow endothelial cells

Abstract: Using a validated tetracycline (tet)-regulated MCF7-founder (MCF7F) expression system to modulate expression of CD44 standard form (CD44s), we report the functional importance of CD44s and that of a novel transcriptional target of hyaluronan (HA)/CD44s signaling, EMS1/cortactin, in underpinning breast cancer metastasis. In functional experiments, tet-regulated induction of CD44s potentiated the migration and invasion of MCF7F cells through HA-supplemented Matrigel. EMS1/cortactin was identified by expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
146
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 40 publications
10
146
0
Order By: Relevance
“…Expression of variant exons 3, 6, 8 and 10 have been associated with the invasive potential of tumors in numerous studies, as reviewed in [19]. However, studies have also indicated that expression of CD44s is associated with breast cancer metastasis [20,21], and there is recent evidence that expression of CD44s accelerates EMT and breast cancer progression [22]. Our data supports the association of CD44s with a mesenchymal phenotype.…”
Section: Discussionsupporting
confidence: 84%
“…Expression of variant exons 3, 6, 8 and 10 have been associated with the invasive potential of tumors in numerous studies, as reviewed in [19]. However, studies have also indicated that expression of CD44s is associated with breast cancer metastasis [20,21], and there is recent evidence that expression of CD44s accelerates EMT and breast cancer progression [22]. Our data supports the association of CD44s with a mesenchymal phenotype.…”
Section: Discussionsupporting
confidence: 84%
“…10 -13 The CD44 -HA complex initiates a series of intracellular signaling events that lead to migration, adhesion, invasion, proliferation, and differentiation of a variety of cells. The transduction of HA/CD44 signaling can occur through various mechanisms including the following: i) HA binding to CD44 can initiate the extracellular clustering of CD44, resulting in the activation of downstream kinases, 14 ii) CD44 can serve as a co-receptor physically associated with other cell signaling receptors, [15][16][17][18] iii) CD44 can serve as a docking protein for pericellular or cytoplasmic proteins, 19,20 and iv) the transmembrane domain of CD44 can be cleaved, allowing the translocation of the cytoplasmic domain to the nucleus, where it functions as a transcription factor regulating the expression of target genes such as CD44 itself. 21,22 CD44 and its variants can induce chemoresistance and invasion of human BC cell lines via different mechanisms.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] Despite knowing the role that CD44 -HA plays in promoting BC invasion and metastasis, the underlying downstream signaling mechanism is nascent. In an attempt to elucidate these downstream signaling mechanisms, we generated a tetracycline (tet)-off-inducible system of CD44 expression both in vitro 14 and in vivo. 16 These studies showed that induction of CD44 potentiated migration and invasion of BC cells 14 and promoted BC metastasis to the liver 16 through the CD44 -HA/NF-B/cortactin signaling pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the functional properties of cortactin, together with amplification of chromosome locus 11q13, suggest a link between its overexpression and tumour invasion and/or metastasis. Accordingly, in several animal models ectopic overexpression of cortactin has been shown to accelerate tumour dissemination, and decreased expression of cortactin, by RNA interference, leads to impaired tumour cell migration and metastasis (Li et al, 2001;Chuma et al, 2004;Hill et al, 2006;Luo et al, 2006).…”
mentioning
confidence: 99%